Growth of Dendrobium nobile Lindl. as related with nutrient concentration in the growing media - Demattê, M. E S P [UNESP]; Graziano, T. T. (My University, 2000)
Dendrobium nobile orchids were grown for three years in different substrates (tree fern fiber, blocks of pressed coconut bark, bark of Eucalyptus grandis, mixtures with coconut bark blocks and eucalyptus bark and mixtures with the latter materials and charcoal. Plant growth increased with higher concentrations of S (up to 1.6 g/kg), Cu (up to 46 mg/kg) and Zn (up to 147 mg/kg), and decreased with higher concentrations of Ca (up to 13.2 g/kg), Mg (up to 6.6 g/kg) and B (up to 19 mg/kg). High Mo (up to 5.3 mg/kg) caused a more intense loss of leaves after planting. Relations between nutrient concentrations also affected plant growth. With exception of eucalyptus bark, all growing media under study were suitable for plant growth.
Keywords: Dendrobium nobile; Growing media; Mineral nutrition; Orchidaceae